(untitled) (Altre Modernità, 2022)
The purpose of this study was to identify problems teaching Chinese as a second language during the unexpected sudden lockdown in 2020 and then to propose strategies for similar future situations and better ways of planning remote teaching programs. The Covid-19 lockdown caused courses at Italian universities that are normally carried out face-to-face to be moved online. This affected language courses particularly severely. This article is focused on the experiences of staff and students involved in three Chinese language courses at two state universities in northern Italy. Background literature about online teaching is analyzed first, then the online teaching methods and tools that were used in the emergency are described and student survey results are assessed. The results are used to identify the strengths and weaknesses of the emergency online teaching provision. The possibility of using self-learning material and watching video-lessons was appreciated, but one of the main drawbacks was the lack of oral and written interaction. Actions for future development are proposed here. These include using asynchronous and synchronous tools to promote active language learning and interaction. An innovative proposal for a long-term teaching program is the flipped classroom, which would allow students to undertake self-learning at home but with a focus on interactions and practical activities during face-to-face classes.